A Hesitant Fuzzy Set Approach to Ideal Theory in Γ-Semigroups - Mohammad Y. Abbasi; Aakif F. Talee; Sabahat A. Khan; Kostaq Hila (Advances in Fuzzy Systems)
We apply the hesitant fuzzy sets theory to Γ-semigroups and provide some characterizations of hesitant fuzzy left (right and bi-) ideals. We introduce the hesitant fuzzy left (resp., right and two-sided) ideal, hesitant fuzzy bi-ideal, and hesitant fuzzy interior ideal in Γ-semigroup and study some properties of them. Finally, a characterization of a simple Γ-semigroup by means of a hesitant fuzzy simple Γ-semigroup is obtained.